2018
DOI: 10.1142/s2424786318500366
|View full text |Cite
|
Sign up to set email alerts
|

The impact of business cycle on capital buffer during the period of Basel-II and Basel-III: Evidence from the Pakistani banks

Abstract: The main objective of this study is to examine the behavior of capital buffer (whether procyclicality or countercyclical) for Pakistani banks after implementation of the BASEL-II and BASEL-III accord. The sample in this study consists of 34 commercial banks of Pakistan during the period from 2006 to 2015. The impact of business cycle on Capital Buffer has been obtained by using the two-step system Generalized Method of Moment estimation technique. The empirical findings suggest that the behavior of the banks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Yet, there are biases in panel regression analysis that may result in conflicting coefficient values. To account for any potential biases, the dynamic panel model would be estimated using a two-step system GMM estimation technique (Iftikhar & Iftikhar, 2018). This method is considered the best panel regression estimation approach since it removes the endogeneity problem by employing lagged values of explanatory variables as instruments to be used in the equation underestimate (Roodman, 2009).…”
Section: Econometric Techniquementioning
confidence: 99%
“…Yet, there are biases in panel regression analysis that may result in conflicting coefficient values. To account for any potential biases, the dynamic panel model would be estimated using a two-step system GMM estimation technique (Iftikhar & Iftikhar, 2018). This method is considered the best panel regression estimation approach since it removes the endogeneity problem by employing lagged values of explanatory variables as instruments to be used in the equation underestimate (Roodman, 2009).…”
Section: Econometric Techniquementioning
confidence: 99%
“…Studies like Ayuso et al (2004), Lindquist (2004), Atici and Gursoy (2011), and Coffinet et al (2012), have found the negative influence of cyclical behavior on the capital buffer, which indicated the shortsightedness of the banks in the period of the Basel-II Accord that increased the risks during the boom period. However, Jokipii and Milne (2011) and Iftikhar (2018) considered the period of Basel-III, and surprisingly, found a positive relationship between the business cycle and capital requirements. After that, they suggested that banks converted their approach from backward-looking to forward-looking aspects because they had taken appropriate and viable measures during the boom period to ensure the exacting stability of the banking industry, but some authors include an important variable of market structure.…”
Section: Introductionmentioning
confidence: 98%